2012
DOI: 10.1186/2008-2231-20-27
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for sulfur mustard lung injuries; new therapeutic approaches from acute to chronic phase

Abstract: ObjectiveSulfur mustard (SM) is one of the major potent chemical warfare and attractive weapons for terrorists. It has caused deaths to hundreds of thousands of victims in World War I and more recently during the Iran-Iraq war (1980–1988). It has ability to develop severe acute and chronic damage to the respiratory tract, eyes and skin. Understanding the acute and chronic biologic consequences of SM exposure may be quite essential for developing efficient prophylactic/therapeutic measures. One of the systems m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 86 publications
3
20
0
Order By: Relevance
“…Lung injury is an ongoing pathological and active disorder even years after exposure to SM. Different drug classes have been studied; nevertheless, there are no curative modalities for mustard lung . Recent studies have shown that bronchiolitis obliterans (BO) is the major cause of respiratory complications following SM exposure.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Lung injury is an ongoing pathological and active disorder even years after exposure to SM. Different drug classes have been studied; nevertheless, there are no curative modalities for mustard lung . Recent studies have shown that bronchiolitis obliterans (BO) is the major cause of respiratory complications following SM exposure.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Proven pathologies are oxidative stress, apoptosis and inflammation. SM-induced oxidative stress results in depletion of low molecular mass antioxidants such as glutathione (GSH) and increase of reactive oxygen species (ROS) (Gould et al, 2009; Laskin et al, 2010; Poursaleh et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Sulfur mustard (bis (2‐chloroethyl) sulfide) is an alkylating vesicant used as a chemical warfare agent, reportedly causing more than 80% of all documented chemical warfare gas casualties in the last century . Sulfur mustard (SM) remains a threat, despite last being used in the Iran‐Iraq War (1979–1988), because it is stockpiled in multiple countries around the world, including the United States, the former Soviet republic, North Korea, Syria, and potentially others.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur mustard (SM) remains a threat, despite last being used in the Iran‐Iraq War (1979–1988), because it is stockpiled in multiple countries around the world, including the United States, the former Soviet republic, North Korea, Syria, and potentially others. SM has acute and chronic harmful effects on the eyes, skin, bone marrow, and respiratory tract . The most acutely threatening injury is damage to the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%